Incursions of southern-sourced water into the deep North Atlantic during Late Pliocene glacial intensification - Lang, DC; Bailey, I; Wilson, PA; Chalk, TB; Foster, GL; Gutjahr, M (Nature Geoscience, 2016)
This is the author accepted manuscript. The final version is available from the publisher via the DOI in this record. Published Online 4th April 2016. The circulation and internal structure of the oceans exert a strong influence on Earth’s climate because they control latitudinal heat transport and the segregation of carbon between the atmosphere and the abyss. Circulation change, particularly in the Atlantic Ocean, is widely suggested to have been instrumental in the intensification of northern hemisphere glaciation when large ice-sheets first developed on North America and Eurasia during the Late Pliocene, ~2.7 million years ago. Yet the mechanistic link and cause/effect relationship between ocean circulation and glaciation are debated. Here we present new records of North Atlantic Ocean structure using the carbon and neodymium isotopic composition of deep waters for both the Last Glacial to Holocene (35-5 thousand years ago) and the Late Pliocene to earliest Pleistocene (3.3 to 2.4 million years ago). Our data show no secular change. Instead we document major southern-sourced water incursions into the deep North Atlantic during prominent glacials from 2.7 million years ago. Our results suggest that Atlantic circulation acts as a positive feedback rather than as an underlying cause of Late Pliocene northern hemisphere glaciation. We propose that, once surface Southern Ocean stratification and/or extensive sea-ice cover was established, cold-stage expansions of southern-sourced water such as those documented here enhanced carbon dioxide storage in the deep ocean, helping to increase the amplitude of glacial cycles. This research was supported by the Natural Environment Research Council (NERC) through a PhD studentship to D.C.L., a NERC UK IODP grant NE/F00141X/1 to P.A.W. and I.B., a Royal Society Wolfson Research Merit Award to P.A.W. and NERC grant NE/H006273/1 to G.L.F.